2009
DOI: 10.1016/s0377-1237(09)80125-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antenatal Expression of Breast Milk at Term in Reducing Breast Feeding Failures

Abstract: Background: Though breast feeding is natural, during the first 2-3 days, when enough breast milk is not available with mother, she may introduce bottle feeding erroneously for improving nutrition to her baby. We studied the effect of antenatal expression of breast milk at term in reducing breast feeding failure as compared to conventional method of initiation of breast feeding. Methods: A prospective study was carried out in 180 booked cases at term. Daily expression of breast milk at least once a day after 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 9 publications
(7 reference statements)
0
37
1
1
Order By: Relevance
“…In spite of knowing the health benefits of mother's milk, most mothers fail to establish early and satisfactory lactation in the initial postpartum period, and formula milk is introduced to the neonates, which hampers the process of lactation, and thus, a vicious cycle starts [4].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In spite of knowing the health benefits of mother's milk, most mothers fail to establish early and satisfactory lactation in the initial postpartum period, and formula milk is introduced to the neonates, which hampers the process of lactation, and thus, a vicious cycle starts [4].…”
Section: Discussionmentioning
confidence: 99%
“…It is feared that antenatal breast milk expression may cause loss of colostrum and may initiate premature contraction leading to preterm onset of labor and also that the infant will lose health benefits of colostrum. Many studies have found that in follow-up of these babies born in group 1, there was no increased incidence of growth compromise [4]. In certain studies, pregnant women are advised to store milk for their infants for postpartum period like in case of diabetic mothers [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations